International Society of Oncology Pharmacy Practitioners global position on the use of biosimilars in cancer treatment and supportive care. (April 2020) - Frazer, Morgan B; Bubalo, Joseph; Patel, Himanshu; Siderov, Jim; Cubilla, Milagros; De Lemos, Mário; Dhillon, Harbans; Harchowal, Jatinder; Kuchonthara, Nirachorn; Livinalli, Annemeri; Macedo, Rodrigo; Mwangi, Winnie; et al.
With the development of innovative cancer treatments over recent decades, the cost of cancer care has risen exponentially, limiting patient access to patented originator biotherapeutics in many countries. The introduction of biosimilars to the market has created new opportunities as well the need for changes in practice within healthcare institutions. A 'biosimilar' is a biotherapeutic product which is highly similar in terms of quality, safety and efficacy to an already licensed originator product. Although biosimilars lack clinically meaningful differences in therapeutic activity as compared to the originator product, these complex biological molecules are not considered identical chemical copies, unlike generics, and minor differences in molecular structure and inactive compounds may exist. A thorough understanding of these differences and their clinical implications is necessary for optimising medicines-use practices involving biosimilars. This position statement, developed by the International Society of Oncology Pharmacy Practitioners Biosimilars Taskforce, aims to provide the global oncology pharmacy community with guidance to support decisions around biosimilar use. The 11 statements cover the regulation and evaluation of biosimilars, practical issues around local implementation, the education of healthcare staff and patients, and the requirement for ongoing pharmacovigilance and outcome monitoring.